Socially-responsible marketing at the enterprises of the construction industry: focus on energy saving - Klymchuk, M.; Shehda, M. (Ways to Improve Construction Efficiency, 2015)
In the article the concept of socially responsible marketing, sustainable deve-lopment, "green" economy in the context of energy saving measures in enterprises building industry. The main directions of solving the problems of energy saving, which is in the plane of the main component of these concepts: economic, environmental and social and will provide an opportunity to effectively establish corporate culture enterprises of the construction industry and provide a synergistic effect of using the latest eco-technologies, both in construction and in the energy sector.